2022
DOI: 10.3390/ijerph192416729
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Per- and Polyfluoroalkyl Substances to Aquatic Invertebrates, Planktons, and Microorganisms

Abstract: Per- and polyfluoroalkyl substances (PFASs), recognized worldwide as emerging pollutants, may pose a substantial threat to human health and our environment due to their stability, high concentrations, wide distribution, and easy accumulation. Ever since perfluorooctane sulfonate and perfluorooctanoic acid were recognized by the Stockholm Convention on Persistent Organic Pollutants, the public has become increasingly concerned about potential contamination and the environmental risks associated with PFASs. Ubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 73 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Therefore, further studies on the neurotoxic effects of PFAS relating to molecular mechanisms and gene expression are necessary. Furthermore, as a low-cost and highly effective model organism, C. elegans should be used in more toxicity tests of other compounds with different carbon chain lengths in the huge PFAS family, including perfluorodecanoic acid, perfluopentanoic acid [72], PFHxA, perfluoropentanesulfonic acid (PFPeS), perfluorohexyl sulfonate (PFHxS), perfluorononanoic acid, perfluorooctane sulfonamide (PFOSA), perfluorododecanoic acid (PFDoA), perfluorodecanoic acid, perfluorodecanoic acid, perfluoroheptanoic acid [67], ammonium perfluorooctanoate, perfluoropropionic acid, fluorotelomer carboxylic acids, fluorotelomer alcohols, perfluoroundecanoic acid, perfluoroethylcyclohexane sulfonate [2], and other short-chain analogs, such as chlorinated polyfluoroalkyl ether sulfonic acids and sodium p-perfluorous nonenoxybenzenesulfonate, widely used as alternatives to PFOS and PFOA [6]. GenX induced physiological effects, including developmental delay, behavior and locomotive effects, and transcriptional effects; however, further comparisons between GenX and the other four PFASs are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further studies on the neurotoxic effects of PFAS relating to molecular mechanisms and gene expression are necessary. Furthermore, as a low-cost and highly effective model organism, C. elegans should be used in more toxicity tests of other compounds with different carbon chain lengths in the huge PFAS family, including perfluorodecanoic acid, perfluopentanoic acid [72], PFHxA, perfluoropentanesulfonic acid (PFPeS), perfluorohexyl sulfonate (PFHxS), perfluorononanoic acid, perfluorooctane sulfonamide (PFOSA), perfluorododecanoic acid (PFDoA), perfluorodecanoic acid, perfluorodecanoic acid, perfluoroheptanoic acid [67], ammonium perfluorooctanoate, perfluoropropionic acid, fluorotelomer carboxylic acids, fluorotelomer alcohols, perfluoroundecanoic acid, perfluoroethylcyclohexane sulfonate [2], and other short-chain analogs, such as chlorinated polyfluoroalkyl ether sulfonic acids and sodium p-perfluorous nonenoxybenzenesulfonate, widely used as alternatives to PFOS and PFOA [6]. GenX induced physiological effects, including developmental delay, behavior and locomotive effects, and transcriptional effects; however, further comparisons between GenX and the other four PFASs are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The presence and persistence of these compounds result in their bioaccumulation and biomagnification at multiple levels within the natural food web, challenging the accurate assessment of ecological risks while accounting for the vast differences in species habitat and compound exposure [ 3 , 4 ]. Perfluorooctanesulfonic (PFOS) and perfluorooctanoic acids (PFOAs) are the most prominent chemical contaminants in this group of synthetic chemicals and are associated with various toxicities and disruptive effects on the immune, metabolic, neural, and endocrine systems of different living organisms [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have highlighted the potential risks of PFAS to affect ecosystem structure and function in aquatic environments, emphasizing the need for further information about their ecotoxicological potential among multiple generations, species interactions, and mixture toxicity [ 60 ]. Furthermore, research has shown that PFAS can have adverse effects on amphibians, aquatic invertebrates, plankton, and microorganisms, indicating a broad impact of PFAS on aquatic ecosystems [ 61 , 62 ]. Additionally, PFAS has been associated with autoimmune-like effects in American alligators, further underlining the potential ecological risks these substances pose [ 63 ].…”
Section: Environmental Occurrence and Ecotoxicological Effects Of Pfasmentioning
confidence: 99%